A label-free aptasensor for the detection of ATP based on turn-on fluorescence DNA-templated silver nanoclusters. Issue 46 (20th October 2022) - Zhang, Baozhu; Yang, Ziyao; Li, Yuxia; Ma, Ling; Li, Fenfang; Lv, Xiuqing; Wen, Guangming
Abstract : A label-free aptasensor has been fabricated in order to detect adenosine triphosphate (ATP) using turn-on fluorescence DNA-Ag NCs. Abstract : A label-free aptasensor has been fabricated in order to detect adenosine triphosphate (ATP) using turn-on fluorescence DNA-Ag NCs. The fluorescence of the DNA-Ag NCs could increase remarkably with the addition of ATP mainly because ATP specifically interacts with its aptamer to change the microenvironment of the darkish DNA-Ag NCs located at one terminus or two termini due to the conformational alteration of the aptamer structure. The proposed sensor can detect ATP in a linear range of 6–27 mM with a good detection limit of 5.0 μM. Additionally, the proposed method succeeded in detecting ATP in fetal bovine serum.